The risk free rate of return in UK property pricing - Hutchison, N.; Fraser, Patricia; Adair, A.; Srivatsa, R. (Emerald Group Publishing Ltd., 2011)
Purpose – The aim of this paper is to consider the appropriate benchmark risk free rate suitable for pricing of property investments in the UK and, in doing so, investigate the financial characteristics and performance of the UK gilt yields. European investors have been significant players in the UK commercial property market during the last decade and in order to be competitive in bidding situations with UK-based investors, require to be aware of the pricing criteria adopted. Design/methodology/approach – This paper analyses the stability, yield distribution and volatility of both conventional gilts and index-linked gilts with different maturities over the period1980-2010. It considers the changing structure of the UK commercial property market and reports on a questionnaire survey of the UK property investment community, which focused on the rationale behind the selection of the appropriate risk free rate of return. Findings – The analysis suggests that ten-year index-linked gilts have been the most stable, but that if conventional gilts are preferred, then five-year nominal appear to be more stable than ten-year nominal; ten-year real yields are smoother and relatively less volatile. In the authors’ survey of the UK property investment fund managers and their advisors, the majority, but by no means all of the respondents, used the ten-year nominal gilt yield as their risk free rate of return. However, questions were raised as to whether it was appropriate to use spot or average gilt yields, particularly when rates in 2009/2010 had fallen to such low level. Originality/value – The findings provide a better understanding of how the different maturities of gilts behave. Insight is given on the criteria adopted by investors when selecting the risk free rate.